(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to investigate the effect of fasting for 4 days on rumen ecology of Nubian goats after two levels of feed restriction (30% and 60% of ad libitum) for 6 weeks. Twelve male Nubian goat kids were divided into three groups according to the level of feed restriction; A (control; ad libitum feed consumption), B (30% feed restriction of ad libitum) and C (60% feed restriction of ad libitum) for 6 weeks. Thereafter, they were exposed to fasting (100% feed restriction) for 4 days. During fasting phase, the three groups showed a significant (p<0.05) decrease in rumen sort-chain fatty acids (SCFA) and osmolality. They exhibited no significant reduction in rumen protozoa count, rumen pH and rumen calcium concentration in response to complete fasting. The concentration of rumen magnesium was not significantly affected by fasting in all the experimental groups. The concentrations of rumen Na+ and K+ were not significantly affected by fasting in group B, while, Group C showed a significant (p<0.05) increase in rumen sodium concentration and a significant decrease in rumen potassium concentration in response to fasting. No serious problems have been observed in the rumen milieu during starvation for 4 days